1976
DOI: 10.1097/00000658-197603000-00010
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomic Basis of Parathyroid Surgery

Abstract: A study of 645 normal adult parathyroid glands in 160 cadavers revealed that there is a definite pattern of anatomic distribution on the basis of the embryologic development of the parathyroid, thyroid, and thymic glands. The sites of predilection of the upper gland (Parathyroid IV) are, in order of frequency, the cricothyroid junction; the dorsum of the upper pole of the thyroid; and the retropharyngeal space. Those of the lower gland (Parathyroid III) are at the lower pole of the thyroid and the thymic tongu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
232
0
29

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 512 publications
(268 citation statements)
references
References 1 publication
7
232
0
29
Order By: Relevance
“…Knowing the anatomical position and vascular supply of the parathyroid glands is essential to avoid hypoparathyroidism after thyroid surgery30, 31. According to a study of 100 cadaveric thyroid glands32, 38.2 per cent of the parathyroid vessels were considered at risk of damage during standard thyroidectomy; the authors reported that the four parathyroid glands were at risk in 5 per cent of the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing the anatomical position and vascular supply of the parathyroid glands is essential to avoid hypoparathyroidism after thyroid surgery30, 31. According to a study of 100 cadaveric thyroid glands32, 38.2 per cent of the parathyroid vessels were considered at risk of damage during standard thyroidectomy; the authors reported that the four parathyroid glands were at risk in 5 per cent of the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The missing inferior parathyroid glands are sometimes found in the thyro-thalamic ligament at the lower pole. In about 5% individuals five rather than four glands may be seen [4,[9][10][11]. The parathyroids are golden yellow in colour and author finds the attached "sentinel pad" of fat a very reliable pointer to the gland ( fig.).…”
Section: Commandment-8: Identify All the Parathyroids And The Rln Tilmentioning
confidence: 99%
“…Mass ligatures should be avoided as there can be accidental inclusion of RLN or damage to the inferior parathyroids (Fig. 10) [9][10][11].…”
Section: Commandment-9: Isolate the Inferior Pedicle And Ligate The Vmentioning
confidence: 99%
“…Они тесно прилежат к щитовидной железе и покрыты общим с ней париетальным листком IV фасции шеи, вследствие чего нередко удаляются при тиреоидэктомии. Верхние ОЩЖ мо-гут также локализоваться ниже верхнего полюса щитовидной железы, ретротра-хеально на уровне средней или нижней трети доли щитовидной железы, над верхним полюсом щитовидной железы, в области бифуркации общей сонной артерии, интратиреоидно [2,7,18,19].…”
unclassified
“…Ряд авторов утверждают, что ОЩЖ расположены ассиметрично [7,18,19], но вместе с тем J.-F. Henry и G. Akerstrum в 60-80% отметили симметричное расположение билатеральных ОЩЖ [16].…”
unclassified